2014
DOI: 10.1158/1538-7445.am2014-2846
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2846: Molecular platforms for mutation analysis from whole blood derived clinical samples by nextgen sequencing

Abstract: Both cell free DNA (cfDNA) and circulating tumor cells (CTC) represent important possible templates for mutation analysis of clinical samples with different theoretical advantages for a clinical test. cfDNA is easy to access and isolate, while CTC can provide both DNA as well as RNA for clinical testing. We have tested matched cfDNA and CTC DNA in a Next Generation sequencing test of clinical samples. Both cfDNA and CTC samples provided sufficient quantity for a direct sequencing clinical test. No whole genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Evidence is accumulating, and analysis of 62 normal and clinically matched samples showed that CTC DNA returned actionable mutations 3 times more often than ctDNA, and ctDNA produced 7 times more false-positive results and 50 times more variation in sensitivity rates than CTC DNA. 151 These are preliminary data; more studies are needed before such a question can be fully answered.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Evidence is accumulating, and analysis of 62 normal and clinically matched samples showed that CTC DNA returned actionable mutations 3 times more often than ctDNA, and ctDNA produced 7 times more false-positive results and 50 times more variation in sensitivity rates than CTC DNA. 151 These are preliminary data; more studies are needed before such a question can be fully answered.…”
Section: Molecular Characterizationmentioning
confidence: 99%